Knowledge Maps - Howard, Ronald A. (Management Science, 1989)
To get fragmented information out of people's heads, onto paper, and ultimately into a computer is a continually challenging problem. We show how to use the concepts of influence diagrams to construct knowledge maps that capture the diverse information possessed by an individual or a group. We use redundant knowledge maps assessed iteratively to handle cases where the most comfortable way to assess the information does not correspond to any proper assessment order for the diagram. We use disjoint knowledge maps when the particular assessment to be made does not require a complete joint distribution. The necessary inferential calculations are readily performed in simple cases by spreadsheet programs. Knowledge maps facilitate the processes of representing knowledge and of determining its implications.